Latin America 2008- 2012. Social investment in education, health services, housing and social assistance as percentage of the gross domestic product (Revista Científica Compendium, 2014)
The aim of this paper is to develop a comparative study of social investment in twenty Latin American Countries. This indicator of social investment is analyzed based on four aspects: (i) education; (ii) health services; (iii) housing; and (iv) social assistance; all of them are identified as percentage of gross domestic products (GDP) of each country. By doing this, it is possible to find out efforts to improve social conditions based on available national resources. Methodological components of this research include comparative analysis with poverty conditions, general statistical indicators, correlation matrix, econometric models, and also the analysis procedures by groups. Countries which shown high levels of social investments are Argentina, Uruguay and Brazil; conversely, those with low standards of social support include: Guatemala, Honduras and Paraguay.
Keywords: social investments; Latin American social and economic conditions; methods of social research